2020
DOI: 10.11646/zootaxa.4790.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of Sphaerodoridae (Annelida) from the Gulf of Thailand

Abstract: Despite being a great species-rich area, the Gulf of Thailand has been relatively poorly studied and new species are awaiting to be described. In the present study two new species of Sphaerodoridae (Annelida), Geminofilum thailandica sp. nov. and Sphaerodoridium songkhlaensis sp. nov. were collected in shallow soft bottoms at Songkhla Sea. Geminofilum thailandica sp. nov. is characterised by bearing sessile and elongated dorsal macrotubercles, arranged in two transverse rows per segment, lacking other dorsal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Meanwhile, the breakpoint detection discovered that the expansion happened in 2007, when the PTC dropped and PNV jumped in the same year (Figure 16a). According to the earlier studies, mangrove forests around the coastal areas of the Thailand Peninsula, which has a dense urban population, e.g., Phuket, Songkhla, and Phang Nga, were converted to residential areas and tourism facilities [124]. In Northern Sulawesi, Indonesia, trend analysis of PTC and PNV data revealed that 291 out of 309 grids (94.14%) showed a negative trend in PTC and positive trend in PNV.…”
Section: Trend Analysis and Breakpoint Detection On Deforested And De...mentioning
confidence: 99%
“…Meanwhile, the breakpoint detection discovered that the expansion happened in 2007, when the PTC dropped and PNV jumped in the same year (Figure 16a). According to the earlier studies, mangrove forests around the coastal areas of the Thailand Peninsula, which has a dense urban population, e.g., Phuket, Songkhla, and Phang Nga, were converted to residential areas and tourism facilities [124]. In Northern Sulawesi, Indonesia, trend analysis of PTC and PNV data revealed that 291 out of 309 grids (94.14%) showed a negative trend in PTC and positive trend in PNV.…”
Section: Trend Analysis and Breakpoint Detection On Deforested And De...mentioning
confidence: 99%